Executive functions in adolescents with gender dysphoria - YAZKAN AKGÜL, GÖZDE; PERDAHLI FİŞ, NEŞE; ERDOĞDU, AYŞE BURCU (My University, 2023)
Aim: Aim of this study is evaluating EF by performing neurocognitive tests, and to identify gender-related differences in EF between adolescents with and without GD. Methods: 8 Female-to-Male transgender adolescents (FtMs), and 14 Male-to-Female transsexual adolescents (MtFs) (Gender Dysphoria Group, GDG) and 29 boys, 21 girls (Control Group, CG), were tested in a cross-sectional study, using the Wisconsin Card Sorting Test (WCST), Controlled Oral Word Association Test (COWAT), and Stroop Color and Word Test (SCWT). The psychiatric diagnoses were established by using the KD-SADS. Results: Among GDG 72.7%, had at least one psychopathology. There weren’t any significant differences in, estimated IQ scores, or WCST subtest scores between the 2 groups. COWAT total word count and SCWT-5 total duration test scores were better in the CG. Conclusion: CG had better performance on verbal fluency and response inhibition whereas no differences found on set shifting abilities. In consideration of the existence of EF-related impairment in adolescents with GD, appropriate support and interventions are expected to improve their adaptation skills and comorbid psychopathologies. These results should be interprete cautiously and additional larger scale studies are needed to obtain more comprehensive data related to gender differences in EF of adolescents with GD.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Davranış Bilimleri; Yaşam Bilimleri; Temel Bilimler; Social Sciences and Humanities; Psychology; Developmental Psychology; Behavioural Sciences; Life Sciences; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Sinirbilim ve Davranış; PSİKOLOJİ, GELİŞTİRME; DAVRANIŞ BİLİMLERİ; Natural Sciences (SCI); Life Sciences (LIFE); PSYCHOLOGY; NEUROSCIENCE & BEHAVIOR; PSYCHOLOGY, DEVELOPMENTAL; BEHAVIORAL SCIENCES; Nöropsikoloji ve Fizyolojik Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Neuropsychology and Physiological Psychology; Social Sciences & Humanities; Developmental and Educational Psychology; Adolescents; executive functions; gender dysphoria; neurocognition